Modifying of iron cast melt - L. Z. Pisarenko (Литьë и металлургия)
The article considers influence of single and complex admixtures of graphitizing modifiers and elements increasing supercooling as well as effect of the level of eutecticity, carbon content and cooling speed on the eutectic crystallization process, structure and characteristics of cast iron. The author alleges to the samples of effective use of ''counter modifying ” in production.